Recognition of Foreign Judgments in China: The Liu Case and the “Belt and Road” Initiative - Brand, Ronald A. (Journal of Law and Commerce, 2019)
In June, 2017, the Wuhan Intermediate People’s Court became the first Chinese court to recognize a U.S. judgment in the case of Liu Li v. Tao Li & Tong Wu. The Liu case is a significant development in Chinese private international law, but represents more than a single decision in a single case. It is one piece of a developing puzzle in which the law on the recognition and enforcement of foreign judgments in China is a part of a larger set of developments. These developments are inextricably tied to the “One Belt and One Road,” or “Belt and Road” Initiative first announced by Chinese President Xi Jinping on a visit to Kazakhstan in 2013. This article traces the development of the Liu case, from the first judgment in California to the decision to recognize and enforce that judgment in Wuhan, China. It then provides the context within which the decision on recognition and enforcement was made, and the way the decision fits within President Xi’s “Belt and Road” Initiative and the pronouncements of the Chinese People’s Supreme Court which have encouraged the recognition and enforcement of foreign judgments as part of that Initiative.